2017
DOI: 10.1016/j.jnucmat.2017.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Solute effects on edge dislocation pinning in complex alpha-Fe alloys

Abstract: Reactor pressure vessel steels are well-known to harden and embrittle under neutron irradiation, mainly because of the formation of obstacles to the motion of dislocations, in particular, precipitates and clusters composed of Cu, Ni, Mn, Si and P. In this paper, we employ two complementary atomistic modelling techniques to study the heterogeneous precipitation and segregation of these elements and their effects on the edge dislocations in BCC iron. We use a special and highly computationally efficient Monte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These studies revealed that Cu, Mn, Ni, and P (Si has not been studied because of the absence of a suitable Fe-Si interatomic potential) naturally tend to accumulate around extended defects, such as dislocation loops and lines. They thus create energetically stable clouds around them, as well as precipitates (the simulations specifically suggest the formation of Cu and NiMn B2 phase precipitates, or Mn-rich regions, attached to dislocation loops and lines) [58,59]. Based on these considerations, we propose here the general scenario illustrated in Fig.…”
Section: Mechanism Driving the Formation Of Nano-sized Solute Rich Cl...mentioning
confidence: 81%
“…These studies revealed that Cu, Mn, Ni, and P (Si has not been studied because of the absence of a suitable Fe-Si interatomic potential) naturally tend to accumulate around extended defects, such as dislocation loops and lines. They thus create energetically stable clouds around them, as well as precipitates (the simulations specifically suggest the formation of Cu and NiMn B2 phase precipitates, or Mn-rich regions, attached to dislocation loops and lines) [58,59]. Based on these considerations, we propose here the general scenario illustrated in Fig.…”
Section: Mechanism Driving the Formation Of Nano-sized Solute Rich Cl...mentioning
confidence: 81%
“…As shown by J. Ke et al ( 2018) [29], RIS results in Ni and Si segregation, which is sufficient to drive precipitation. However, it should be noted that thermal segregation and precipitation, which is greatly accelerated by RED, could also be significant [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…Solute atoms are considered to affect recovery via solute drag effect on dislocation motion [51]. The solute segregation around dislocation cores pins dislocations, making them sessile and a high driving pressure is then required for the dislocations to escape from the solute environment [52,53,54,55,56]. Takeuchi et al [57] and Nabarro [58] theoretically treated the solute drag effect on a climbing and a gliding dislocation.…”
Section: Discussionmentioning
confidence: 99%